2020
DOI: 10.1093/gji/ggaa296
|View full text |Cite
|
Sign up to set email alerts
|

3-D joint inversion of seismic waveform and airborne gravity gradiometry data

Abstract: Summary Seismic full waveform inversion is a robust velocity model building technique for hydrocarbon exploration. However, the density reconstruction within the framework of multiparameter full waveform inversion leads to more degrees of freedom in the parameterization, and the sensitivity of the inversion change significantly from velocity to density, thereby increasing the ill-posedness of the inverse problem. Gravity gradiometry data inversion is an effective method for resolving density dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Jiang developed a 3D joint seismic waveform and gravity gradiometry inversion method. A case study in the South China Sea showed that joint inversion results are consistent with the pre-stack depth migration section, and the shape of the salt body is well resolved [31].…”
Section: Introductionmentioning
confidence: 66%
“…Jiang developed a 3D joint seismic waveform and gravity gradiometry inversion method. A case study in the South China Sea showed that joint inversion results are consistent with the pre-stack depth migration section, and the shape of the salt body is well resolved [31].…”
Section: Introductionmentioning
confidence: 66%
“…Although wave equation-based traveltime inversion methods [5,6] could provide a better near-surface velocity model because they account for the phase difference, the computation cost is much more expensive because of the wave equation calculation. The refraction traveltime tomography result can also be utilized in geological surveys [7], initial velocity models for early-arrival waveform inversion (EWI) [8][9][10], joint geophysical inversion [11], and medical imaging [12].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the convergence of the multiparameter FWI, ref. [27] used the cross-gradient method to perform the multi-parameter inversion of the variable-density acoustic wave equation, and ref. [28] adopted the truncated Gauss-Newton method to reconstruct velocity and density simultaneously.…”
Section: Introductionmentioning
confidence: 99%